Confronting Mean Girls Niceness: Conceptualizing Whisper Care to Disrupt the Politics of Niceness in Academia - Rose Ann E. Gutierrez; Carolyn S. F. Silva; Ruby Batz (MDPI AG, 2024)
While the current literature on Niceness in higher education has examined the discourses and practices of Niceness in academic spaces, making it more identifiable, less is known about how minoritized faculty navigate and disrupt the culture of Niceness. The purpose of this article is to offer a resistance-based framework to combat academia's Niceness culture through the lens of the authors. Using theory in the flesh as theory and methodology, we use collaborative autoethnography to conceptualize Whisper Care to give language and articulate an orientation and philosophy rooted in Kindness. Our findings present a process to confront Niceness while guiding, supporting, and protecting each other in higher education institutions. We conclude with implications for future research and practice for faculty and higher education leaders.